2014
DOI: 10.1002/mop.28327
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic coaxial transmission line and phase shifter

Abstract: This article presents a microfluidic coaxial transmission line assembly that is realized by weaving together stretchable metallic fibers composed of a liquid‐metal core inside an elastomeric shell. These fibers are woven around a core fiber to create a coaxial assembly. The resulting structure exhibits exceptional stretchability compared to conventional coaxial transmission lines. The mechanical properties of the supporting elastomer and the fluidic properties of the conductors ensure that the characteristic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The spectral properties of an antenna are a function of its shape; thus the ability to both physically deform and manipulate the shape of liquid metal offers unique possibilities for tunable and reconfigurable antennas. Liquid metal injected into microchannels has been utilized to make many types of antennas including dipoles ( Figure a,b), loops (Figure c), coils and inductors (Figure d), patch antennas (Figure e), radio‐frequency antennas (Figure f), spherical caps, phase shifting coaxial transmission lines, monopoles, and reconfigurable antennas and filters . There are many more examples that utilize Hg.…”
Section: Stretchable Antennasmentioning
confidence: 99%
“…The spectral properties of an antenna are a function of its shape; thus the ability to both physically deform and manipulate the shape of liquid metal offers unique possibilities for tunable and reconfigurable antennas. Liquid metal injected into microchannels has been utilized to make many types of antennas including dipoles ( Figure a,b), loops (Figure c), coils and inductors (Figure d), patch antennas (Figure e), radio‐frequency antennas (Figure f), spherical caps, phase shifting coaxial transmission lines, monopoles, and reconfigurable antennas and filters . There are many more examples that utilize Hg.…”
Section: Stretchable Antennasmentioning
confidence: 99%
“… 78 82 Our group 83 and others 84 86 showed that it is possible to form stretchable antennas using the metal. A variety of antennas are possible including patch antennas (useful for GPS), 87 phase-shifting coaxial cables, 88 coil antennas (useful for wireless power transfer), 89 unbalanced loop antennas, 84 frequency selective surfaces, 90 and plasmonic structures. 91 , 92 Figure 7 shows photographs of several examples of liquid metal antennas.…”
Section: Applicationsmentioning
confidence: 99%
“…Previously, patterning of liquid metals by direct writing and filling predefined microchannels has been demonstrated . Furthermore, the use of liquid metal as conductors, capacitors, and antennas has been shown. The illustrated circuit and sensor applications include embedded elastomer conductors, hyperelastic pressure sensors, stretchable radiation sensors, passive wireless sensors, deformable and tunable fluidic antennas, and tactile interfaces …”
mentioning
confidence: 99%